2015
DOI: 10.12693/aphyspola.127.1320
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Coating Formed on Pure Zirconium by MAO in Yttrium Acetate Tetrahydrate Containing Electrolyte

Abstract: In this study, oxide coatings were produced on pure zirconium by micro arc oxidation method in the electrolytes containing sodium silicate and dierent amounts of yttrium acetate tetrahydrate (14 g/l) for the same coating duration of 1 h. The surface roughness, microstructure, phase content and chemical composition of the coatings were characterized by using scanning electron microscopy, prolometry and X-Ray diractometry. It was found that the surfaces of coatings on zirconium consist of monoclinic-ZrO2, tetrag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Though t-ZrO 2 is a high temperature phase, its stabilization at room temperature was attributed to several mechanisms such as reduction of grain size, residual compressive stresses and existence of oxides in the Zr-O phases like MgO, Y 2 O 3 and CaO [17]. However, the clear effect of CA addition on the XRD peaks obviously resulted in dominance of t-ZrO 2 phase in the coating surface in this study (Fig.…”
Section: Phase Analysis Of Coatingsmentioning
confidence: 64%
See 1 more Smart Citation
“…Though t-ZrO 2 is a high temperature phase, its stabilization at room temperature was attributed to several mechanisms such as reduction of grain size, residual compressive stresses and existence of oxides in the Zr-O phases like MgO, Y 2 O 3 and CaO [17]. However, the clear effect of CA addition on the XRD peaks obviously resulted in dominance of t-ZrO 2 phase in the coating surface in this study (Fig.…”
Section: Phase Analysis Of Coatingsmentioning
confidence: 64%
“…The coating/substrate interface became smoother and surface roughness tended to decrease as the amount of YAT in electrolytic solution increased. The XRD results indicated that the coatings were mainly composed of m-ZrO 2 and t-ZrO 2 phases [17]. It was reported that the increasing amount of sodium aluminate (8-32 g/l) in the electrolyte resulted in a higher coating growth rate and the main phases in the coatings were found to be t-ZrO 2 and γ-Al 2 O 3 [18].…”
Section: Introductionmentioning
confidence: 94%
“…For this purpose, various surface treatment techniques including physical or chemical vapor deposition, sol-gel process, thermal oxidation, anodization and plasma electrolytic oxidation (PEO) have been employed to enhance the corrosion resistance and the bioactivity [9,10,12,15,[17][18][19][20][21][22]. Among these surface treatment methods, PEO offers more advantages because it produces well-adhered, crystalline, dense, and thick coating layers with high tribological performance and high thermal-chemical stability [23][24][25][26][27][28][29][30][31][32][33][34][35]. Cheng et al [36] studied the corrosion resistance of a ZrO 2 coating fabricated on Zircolay 4 (Zr-1.2-1.7 wt.% Sn) using a PEO method.…”
Section: Introductionmentioning
confidence: 99%
“…Stabilizing additives can be added to the coating composition not only from the slurry electrolytes. In [ 84 ], oxide coatings were produced on pure zirconium by the microarc oxidation method in the electrolytes containing sodium silicate and different amounts of yttrium acetate tetrahydrate (YAT). The electrolytes with four different compositions were prepared by using a certain amount of sodium silicate and a variable amount of YAT by dissolving them in distilled water as given in Table 8 .…”
Section: Formation Of Oxide-ceramic Layers On the Surface Of Zr And I...mentioning
confidence: 99%
“…Reprinted with permission from Ref. [ 84 ]. 2014, Proceedings of the 4th International Congress APMAS2014.…”
Section: Figurementioning
confidence: 99%